Symmachia basilissa basilissa Bates, 1868 (Riodinidae: Symmachiini) has been photographed while alive for the first time, uncovering a new record and shedding light on its conservation aspects - Neves, Antonio Leal Silva das; Marinho, Lucas Cardoso; Muniz, David Barros (EntomoBrasilis, 2023)
This work reports the first photographic record of the Symmachia basilissa basilissa Bates, 1868 subspecies, a butterfly originally described by Henry Walter Bates in 1868. This subspecies had only been recorded three before but had never been photographed alive in Brazil. The photograph was taken in the Chapada das Mesas National Park, located in the southern part of the state of Maranhão. This record was uploaded and georeferenced on the iNaturalist app/website. The taxon Symmachia basilissa comprises four subspecies, and the article provides information on the morphological differences between them. We also discuss the use of iNaturalist and similar tools to integrate academic and citizen science for a better understanding of biodiversity, especially in tropical regions and areas that are difficult to access. Overall, our work makes a valuable contribution to the knowledge of this data deficient butterfly species and highlights the importance of utilizing new technologies and collaborative approaches to advance scientific research.